The Effect of Financial Literacy on the Decision to Pay ZISWAF Using QRIS in Medan City - Daulay, Melati; Khairunnisa, Khairunnisa (Al-Muhtarifin: Islamic Banking and Islamic Economic Journal, 2022)
This study aims to analyze the effect of financial literacy on the decision to pay ZISWAF using QRIS in medan cities. This research is of the quantitative type which uses primary data as a reference. The population used was people domiciled in Medan cities with a sample of 163 respondents. In sampling, this study uses a probability sampling technique with the cluster sampling methodwhich is carried out if the object to be studied is very broad such as regencies / cities and in this case the research carried out is on all communities domiciled in Medan cities.The results of this study show that the Financial Literacy variable (X) has a positive and significant effect on the ZISWAF Pay decision variable using QRIS (Y) witha calculated tvalue (5.815) ttable (1.974) and a significant value of 0.001 0.005. The simultaneous test on the Financial Literacy variable (X) stated that there was a significant influence together on the ZISWAF Pay decision variable using QRIS in Medan City (Y) witha calculated Fvalue (33.809) Ftable (3.899) and a significant value of 0.001.This study aims to analyze the effect of financial literacy on the decision to pay ZISWAF using QRIS in medan cities. This research is of the quantitative type which uses primary data as a reference. The population used was people domiciled in Medan cities with a sample of 163 respondents. In sampling, this study uses a probability sampling technique with the cluster sampling methodwhich is carried out if the object to be studied is very broad such as regencies / cities and in this case the research carried out is on all communities domiciled in Medan cities.The results of this study show that the Financial Literacy variable (X) has a positive and significant effect on the ZISWAF Pay decision variable using QRIS (Y) witha calculated tvalue (5.815) ttable (1.974) and a significant value of 0.001 0.005. The simultaneous test on the Financial Literacy variable (X) stated that there was a significant influence together on the ZISWAF Pay decision variable using QRIS in Medan City (Y) witha calculated Fvalue (33.809) Ftable (3.899) and a significant value of 0.001.